Advanced Materials in Engineering: A Bibliometric Review - Loso Judijanto (Westscience Press, 2026)
This bibliometric review examines the field of advanced materials in engineering, focusing on the evolution, key trends, and future directions. By applying bibliometric techniques such as citation analysis, co-authorship networks, and keyword co-occurrence, this study identifies influential papers, authors, and research themes in the domain. The findings reveal the growing prominence of sustainable materials, energy storage technologies, and biomedical applications, with energy-related materials, such as lithium-ion batteries, receiving significant attention. The increasing integration of computational methods, including machine learning and density functional theory, highlights the role of data-driven approaches in accelerating material discovery. Additionally, the study underscores the importance of interdisciplinary collaborations across engineering, chemistry, and biology to address global challenges. This review offers valuable insights for researchers and professionals, pointing to emerging trends in advanced materials research and their potential impact on technological and societal advancements.